Micellar dissociation of TPGS-1000 in water: system dynamics or micelle-solvents interaction - Azman, Nur Fatin Amanina (2015)
Three different series of TPGS-1000 that are series A, B and C with different concentration were prepared by using the simple dilution method in which the distilled water was directly added to the surfactant, TPGS-1000. This study deals with the system dynamics and the micelles-solvent interaction involving the TPGS- 1000 and deionised water. The experimental parameters such as the viscosity, activation energy, the AF and B1 constant representing the micelle-micelle and micelle-solvent interactions, the molar volume, and the Mand K constant which give the interaction between the micellar fragment and solvent, have been studied and estimated to understand the system dynamics and the solute-solvent interactions within a solution system. It is observed that the obtained data can be described as micellar dissociation. The measured parameters, those complimented each other have been discussed in terms of the surfactant-solvent interactions which in turn support the occurrence of micellar dissociation.